Rights of Foreign Citizen Heirs to Land in Indonesia: analysis of Supreme Court Decision Number 105/PK/TUN/2013 - Wulan Valentina, Ratna; Arum Prastyanti, Rina (Greenation International Journal of Law and Social Sciences, 2024)
Foreigners' inheritance rights to land in Indonesia is a complex topic and is regulated by strict legal regulations. The method that I will use is the Library Research method. Secondary data such as primary legal materials, secondary legal materials and tertiary legal materials will be used as the main data source. You can carry out analysis directly on informants using analysis guidelines that have been prepared in advance. The following is a summary of the inheritance rights of foreigners and the implications of Supreme Court Decision Number 105/PK/TUN/2013. Principles of Inheritance According to the Civil Code (KUHPerdata), all heirs, including foreigners, have the same right to receive a share of inheritance without regard to gender or nationality (Article 852 of the Civil Code). Land and Buildings Foreigners have the right to receive inheritance in the form of land and buildings which are the property of the heir who is an Indonesian citizen. However, within one year, foreigners must transfer their rights to Indonesian citizens or change the land status to use rights (Article 21 Paragraph (1) & (3) Law No. 5 of 1960 concerning UUPA). Ownership restrictions only apply to Indonesian citizens who have ownership rights to land in Indonesia. Foreigners are not permitted to legally hold land ownership rights (Article 21 Paragraph (1) UUPA). Consequently, if a foreigner does not relinquish land ownership rights within one year after receiving the inheritance, these rights will be forfeited and the land will become state property (Article 21 Paragraph (3) UUPA). The heirs of foreign citizens have the right to inherit the house from the heirs of Indonesian citizens. However, they must waive it within one year to legally retain those rights. Even though these limits are strict, alternatives such as transferring rights to Indonesian citizens or changing status to use rights are still available to avoid ongoing legal consequences. Thus, Supreme Court Decision Number 105/PK/TUN/2013 emphasizes that although foreign heirs have the right to receive an inheritance, they must transfer their rights or change the status of the land within a short time to avoid losing these rights by law.